Analysis on dynamic behavior of 400 km/h high-speed train system under differential settlement of subgrade. (1st March 2023) - Zhang, Keping; Zhang, Xiaohui; Zhou, Shunhua
Highlights: An efficient and accurate vehicle-track-subgrade spatial coupled dynamics model is constructed. Combined with the fixed interface modal synthesis method and wheel/rail contact theory, the joint simulation of ABAQUS and UM is realized. Take the average value of 10 groups of irregularities for track irregularity. System dynamic characteristics of the 400 km/h and 350 km/h vehicle speeds under subgrade differential settlement conditions are compared. The increase of train speed has a great impact on the vertical acceleration of rail. Abstract: Whether the existing ballastless track subgrade settlement control standard of 350 km/h is applicable to the high-speed train of 400 km/h remains to be further research. This paper established a complete rigid flexible coupling dynamic model of vehicle-track-subgrade space based on the finite element method and multi-body dynamics theory. Combined with the fixed interface modal synthesis method and wheel/rail contact theory, the joint simulation of ABAQUS and UM is realized. The dynamic response of 400 km/h high-speed train under the condition of subgrade differential settlement is analyzed and compared with the current 350 km/h high-speed train. The results show that under the same subgrade differential settlement condition, when the train speed increases from 350 km/h to 400 km/h, the wheel rail interaction increases significantly, but does not exceed the specification limit. The amplitude of derailment coefficient is far lower than the maximum specification limit, while the amplitude of wheel load reduction rate exceeds the quasi-static limit in the specification. The impact of the increase of train speed on the lateral stability of the vehicle is greater than that on the vertical stability of the vehicle. At 400 km/h, each stability index of the train does not exceed the maximum specification limit, and sufficient safety margin is reserved. The increase of train speed has a great impact on the vertical acceleration of rail, and has little impact on the vertical acceleration of track plate and baseplate. In summary, the current subgrade settlement control standard of 350 km/h high-speed railway is also applicable to 400 km/h high-speed trains, and there is room for further speed increase.